Oxygen reduction activity and methanol tolerance of carbon-supported PtV nanoparticles and the effects of heat treatment at low temperatures - Gentil, R. [UNESP]; Villullas, H. M. [UNESP] (Springer Nature, 2016)
This paper reports on oxygen reduction activity and methanol tolerance of PtV/C prepared by a polyol method and the effects of heat treatments in reducing environments at low temperatures (up to 300 °C). The as-prepared catalyst showed a low content of alloyed vanadium, but it was considerably more active for the oxygen reduction reaction than Pt/C and had superior methanol tolerance. Dispersive X-ray absorption spectroscopy measurements around the Pt L3 edge indicated that the presence of vanadium in the catalyst increased the Pt 5d-band vacancy at the time that it seems to diminish the Pt coverage by adsorbed OH species. Heat treatments at 150, 200, and 300 °C carried out in strongly reducing conditions produced minor changes in the degree of alloying together with a moderate particle growth. The largest incorporation of vanadium in the alloyed phase was observed after heating at 150 °C while a decrease in the alloying and Pt segregation to the surface were observed for higher treatment temperatures. In general, heat treatments were detrimental for oxygen reduction activity, suggesting that the presence of vanadium oxides might play a role. In addition, the decreased in methanol tolerance might be associated to Pt segregation to the surface.
Keywords: Methanol tolerance; Oxygen reduction; Pt alloys; Pt-based catalyst